Skutki prawne naruszenia w ogólnym postępowaniu administracyjnym zasad stadium rozpoznawczego - Rudnicki, Marcin (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The paper’s aim is to lay down the effects of the infringement of the rules that govern the exploratory stage in the general administrative proceedings.Strictly theoretical deliberations on the characteristics and division of basic standards will serve as a starting point for further considerations. The following section of the paper will deal with the aftermath of infringement of procedural regulations; including the rules applicable in exploratory stage; regarding the correctness of decisions made. The last section of the paper will develop the thesis included in the title of this paper. This shall be done by defining the consequences of infringing norms. These consequences will be discussed taking into consideration both the competencies and merit of public offices, and the nature and extent of the ruling of administrative courts that control public offices.The paper in its main part consists of the author’s own deliberations based on the thesis presented in judicial proceedings and the most prominent voices in the doctrine. Emphasis is also put on references to achievements in other legal areas.
Keywords: ogólne postępowanie administracyjne; skutki prawne; naruszenie zasad stadium rozpoznawczego